A Review Paper on Laminated Composite Plates: A Comprehensive Review of Structural Behavior and Theoretical Analyses of Laminated Composite Plates (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present paper, essential terminology of laminated composite plates are examined. Laminated composite plate structures discover various applications in aviation, military and automotive industries. The part of transverse shear is vital in composites, as the material is frail in shear because of its low shear modulus contrasted with extensional unbending nature. Subsequently, a precise comprehension of their auxiliary conduct is required, for example, deflections and stresses. From the present Literature Review the effect of bending, buckling, thermal and hygrothermal on composite plates examined and diverse speculations like Classical Plate Theory, First Order Shear Deformation Theory and Higher order Shear Deformation Theory and so on for examination of composite plate are specified.